Populus euphratica - a Promising Species for Pulpwood Plantation - Chaturvedi, A. N. (Indian Forester, 1997)
Importance of Populus euphratica for pulpwood plantation and its proximate chemical analysis, strength characters and basic density fibre dimensions are presented in detail in this paper.